Post operative atrial fibrillation - Cosgrave, John (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2006)
Post operative atrial fibrillation is a common occurrence following all forms of cardiac surgery apart from heart transplantation. Coronary artery bypass is the commonest cardiac surgical procedure with more than 800,000 cases performed per year worldwide. The incidence of post coronary artery bypass atrial fibrillation varies depending on the definitions used, but ranges from 10 to 40% of patients. This arrhythmia may terminate spontaneously and have no consequences however in some it causes significant morbidity and may even increase mortality. Thus it can be seen that with a potential incidence of up to 320,000 cases per year this arrhythmia imposes a significant burden on our health care systems. Despite many theories the precise aetiology remains unknown; this thesis will investigate some of the current theories for the development of atrial fibrillation.
Keywords: Clinical Medicine, M.D.; M.D. Trinity College Dublin